2017
DOI: 10.2109/jcersj2.17070
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for joining aluminum and silicon nitride by polysiloxane

Abstract: This paper describes a novel method for joining aluminum and silicon nitride using a polysiloxane. The X-ray diffraction patterns suggested that the polysiloxane surrounded by aluminum and silicon nitride powders could be transformed into silicon, aluminum silicate, and SiAlON. Neither cracks nor exfoliation between aluminum and silicon nitride could be observed, and they were joined through the joining layer. Moreover, detailed investigation of the layer by transmission electronic microscopy, selected area el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…There was no crack between the pure aluminum and silicon nitride. This result was almost the same as our previous report 9 …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There was no crack between the pure aluminum and silicon nitride. This result was almost the same as our previous report 9 …”
Section: Resultssupporting
confidence: 93%
“…Samples for the four‐point bending test, which were standardized as JIS R 1601:2008, were also prepared. The detailed preparation process of these samples has been reported previously 8,9 . A surface area of 600 mm 2 square on two commercially available bulk silicon nitride boards (SN‐210; Japan Fine Ceramics Co., Ltd., Japan) with a size of 20 × 30 × 20 mm was abraded using a grinder.…”
Section: Methodsmentioning
confidence: 99%
“…We note that our previous study into the joining of aluminum and alumina suggested that these species could be joined together through an aluminum silicate layer containing aluminum, silicon, and oxygen atoms. 18,19 In addition, we found that the width of the joining layer was ~100 nm, which is equivalent to the distance between the interlayer and point 2 in the TEM image. It is therefore reasonable to assume that the joining layer in this study is similar, if not the same as, the layer described in our previous study.…”
Section: F I G U R Ementioning
confidence: 78%
“…18 This joining method is applicable not only to oxide ceramics, such as alumina, but also to non-oxide ceramics such as silicon nitride. 19 We therefore believed that our joining method would be suitable for the sintering of porous alumina because the polysiloxane present between the aluminum and alumina species can be transformed into a joining layer by heating at a temperature as low as 600°C, 18,19 and alumina can be formed from aluminum by heating under air.…”
Section: Introductionmentioning
confidence: 99%
“…The most common alloys are 2024, 7075 and 6061 of which only 6061 has 0.6% Si in its specification, and 2024 and 7075 have 1.5 and 2.5 Mg, respectively. There is increasing interest now in inherently compatible materials such as AlN and Si 3 N 4 of which AlN is inherently stable and Si 3 N 4 forms thin, stable AlN or SiAlON boundary layers [15,16]. Lastly, is the utilisation of fibrous reinforcements for improved performance both continuous for high-value applications and discontinuous-short fibre reinforcements for high-volume applications [17,18].…”
Section: Introductionmentioning
confidence: 99%